Methanobrevibacter oralis: a comprehensive review - Virginie Pilliol; Boualam Mahmoud Abdelwadoud; Hamieh Aïcha; Tellissi Lucille; Aboudharam Gérard; Tassery Hervé; Drancourt Michel; Grine Ghiles; Terrer Elodie (Journal of Oral Microbiology)
Methanobrevibacter oralis (M. oralis) has predominated human oral microbiota methanogenic archaea as far back as the Palaeolithic era in Neanderthal populations and gained dominance from the 18th century onwards. M. oralis was initially isolated from dental plaque samples collected from two apparently healthy individuals allowing its first characterization. The culture of M. oralis is fastidious and has been the subject of several studies to improve its laboratory growth. Various PCR methods are used to identify M. oralis, targeting either the 16S rRNA gene or the mcrA gene. However, only one RTQ-PCR system, based on a chaperonin gene, offers specificity, and allows for microbial load quantification. Next-generation sequencing contributed five draft genomes, each approximately 2.08 Mb (±0.052 Mb) with a 27.82 (±0.104) average GC%, and two ancient metagenomic assembled genomes. M. oralis was then detected in various oral cavity sites in healthy individuals and those diagnosed with oral pathologies, notably periodontal diseases, and endodontic infections. Transmission pathways, possibly involving maternal milk and breastfeeding, remain to be clarified. M. oralis was further detected in brain abscesses and respiratory tract samples, bringing its clinical significance into question. This review summarizes the current knowledge about M. oralis, emphasizing its prevalence, associations with dysbiosis and pathologies in oral and extra-oral situations, and symbiotic relationships, with the aim of paving the way for further investigations.